A Promiscuous Cytochrome P450 Hydroxylates Aliphatic and Aromatic C−H Bonds of Aromatic 2, 5‐Diketopiperazines. (27th March 2019) - Jiang, Guangde; Zhang, Yi; Powell, Magan M.; Hylton, Sarah M.; Hiller, Nicholas W.; Loria, Rosemary; Ding, Yousong
Abstract: Cytochrome P450 enzymes generally functionalize inert C−H bonds, and thus, they are important biocatalysts for chemical synthesis. However, enzymes that catalyze both aliphatic and aromatic hydroxylation in the same biotransformation process have rarely been reported. A recent biochemical study demonstrated the P450 TxtC for the biosynthesis of herbicidal thaxtomins as the first example of this unique type of enzyme. Herein, the detailed characterization of substrate requirements and biocatalytic applications of TxtC are reported. The results reveal the importance of N‐methylation of the thaxtomin diketopiperazine (DKP) core on enzyme reactions and demonstrate the tolerance of the enzyme to modifications on the indole and phenyl moieties of its substrates. Furthermore, hydroxylated, methylated, aromatic DKPs are synthesized through a biocatalytic route comprising TxtC and the promiscuous N ‐methyltransferase Amir_4628; thus providing a basis for the broad application of this unique P450. Abstract : Enzymatic aliphatic and aromatic hydroxylation : The cytochrome P450 enzyme TxtC is unique for both aliphatic and aromatic hydroxylation on herbicidal diketopiperazine thaxtomin D. This study reveals the substrate scope, reaction promiscuity, and biocatalytic application of this synthetically valuable enzyme.